KARAKTERISASI FISIKOKIMIA DAN LAJU DISOLUSI DISPERSI PADAT IBUPROFEN DENGAN PEMBAWA POLIETILENGLIKOL 6000 - Erizal Zaini; Rahmi Nofita; Salman Salman; Ima Kurniati (Universitas Islam Indonesia, 2009)
ABSTRACTSolid dispersions of the antiinflamation drug ibuprofen and polyethylene glycol 6000 (PEG6000) were prepared by the melting method in order to increase the dissolution rates of this poorlywater-soluble compound. The temperature/composition phase diagram of binary system wasanalyzed by termal analysis hot-stage microscopy, showing an eutectic formation. Polarized lighthot stage microscopy and X-ray-powder diffraction confirmed, that solid dispersion techniquedecrease the crystalliny of ibuprofen after melting and solidifying of a 4/6 (w/w) mixture of ibuprofenand polyethylene glycol 6000 respectively, which the results enhanced dissolution rates comparedto the physical mixtures and ibuprofen intact. However, no such chemical interactions in the solidstate were confirmed by FTIR spectra which showed the presence of ibuprofen crystalline in soliddispersion.Keywords: solid dispersions, ibuprofen, polyethylene glycol 6000